DC-link capacitor second carrier band switching harmonic current reduction in two-level back-to-back converters - Shen, Lei; Bozhko, Serhiy; Hill, Chris; Wheeler, Patrick (IEEE, 2017)
This paper proposes an active switching harmonic current reduction method within the DC-link capacitor of two-level, three-phase, back-to-back converters. The method is based on the derived analytical solution for switching harmonic currents in the DC-link. It is shown that by controlling the PWM carrier waveform’s phase angles, the harmonics in the 2nd carrier band of the rectifier and the inverter can be synchronized such that cancellation occurs in the DC-link capacitor. This synchronization is provided by harmonic phase feedback control. The feasibility of the proposed approach has been verified experimentally and results are presented in the paper